Assumptions of Objective Reality in Logical Positivism - Sutanto; Abul Hasan Seknun (Journal of Legal Contemplation, 2026)
Logical positivism, as a 20th-century philosophical movement, posits that legitimate scientific knowledge can only be acquired through empirical verification and logical reasoning, while claims that cannot be tested or verified are considered meaningless. A central assumption in logical positivism is the concept of objective reality, which asserts that the external world exists independently of human subjectivity and can be understood through observation and scientific laws that are verifiable. This article explores the foundational assumptions regarding objective reality within logical positivism, focusing on the contributions of key figures such as Rudolf Carnap, Moritz Schlick, and A.J. Ayer. These philosophers argued that the physical world operates according to universal laws that can be verified through structured scientific methods. However, logical positivism has faced criticism, particularly concerning the principle of verificationism and its inability to accommodate the complexities of scientific theories that are not always directly verifiable. Critics such as Karl Popper and Willard Van Orman Quine have raised important questions about the relationship between theory, observation, and objective reality in science. Overall, while logical positivism has laid a significant foundation for modern scientific thought, it also faces profound challenges related to the limitations of verification theory and scientific objectivity.